Evaluasi Program BLT Dana Desa sebagai Jaring Pengaman Sosial Di Desa Kemlagi, Kabupaten Mojokerto - Sri Wibawani; Felixtha Hernanda; Rayhan Gunadewa Kusuma; Fanny Andrianto Irawan (Syntax Idea, 2021)
The purpose of this study was to determine the evaluation of the Village Fund Direct Cash Assistance (BLT) distribution program as a Social Safety Net in Kemlagi Village, Mojokerto Regency. In this study, the authors used qualitative research methods. Qualitative research methods. The qualitative research method is a research method that has become a scientific tradition as a research method in the fields of socio-cultural sciences, psychology, and education. The data analysis technique in this research is a qualitative descriptive analysis technique, the evaluation of the BLT-Village Fund Program has lightened the burden on the community, therefore The effectiveness criteria in Dunn's evaluation theory have achieved the expected goals, Efficiency The action of the village government in order to achieve the goal is to allocate a budget from the central government to the local government which is then channeled to the village fund.